A review about pretreatment of lignocellulosic biomass in anaerobic digestion: Achievement and challenge in Germany and China. (25th May 2021) - Cai, Yafan; Zheng, Zehui; Schäfer, Franziska; Stinner, Walter; Yuan, Xufeng; Wang, Hongliang; Cui, Zongjun; Wang, Xiaofen
Abstract: Lignocellulosic biomasses (LBs) gradually become the vital substrate for the anaerobic digestion (AD) to produce clean bio-energy. However, the low biodegradability of LBs limits their application in the AD. Pretreatment is an essential step to loosen or break the compact structure of LBs before they are used to the AD. The review comprehensively analyzes the development, application and challenge of different pretreatment methods based on the main characteristics (mainly moisture, lignocellulose, and water-soluble carbon content) of different LBs in China and Germany. Pretreatment can shrink the crystallinity of cellulose, lignin content, and increased specific surface area, which make LBs more easily to be degraded by microorganisms. High energy consumption, potential environmental risks and low efficiency are the main shortcomings of physical, chemical, and biological pretreatment, respectively. Energy crops (mainly green maize and energy grasses) are the main LBs in Germany. Mechanical pretreatment and ensiling are used to almost all large-scale biogas projects (LSBPs). In China, the main LBs are maize, wheat and rice straw. Among all physical pretreatments, only mechanical pretreatment was used widely. The possible secondary pollution caused by chemical pretreatment limited its application. Among all biological pretreatments, the ensiling and microaerobic pretreatment of withered crop straw is still at the early stage of research. Microbial consortium pretreatment, especially for biogas slurry pretreatment, is most likely to be applied among microbial pretreatments because of its economic viability, environmental friendliness, and high operability. The combination pretreatment mode should be explored in future research and is the most promising pretreatment mode in China. The characteristics of LBs in China and Germany are different, which leads to varying greatly in pretreatment methods. A comprehensive analysis of the two countries' pretreatment modes can provide references for other countries with similar substrate characteristics. Graphical abstract: Image 1 Highlights: Crop straws and energy crops are the main LBs in China and Germany, respectively. LBs' features should be first considered to select the pretreatment method. Mechanical crushing and ensiling are main pretreatment methods for energy crops. Combined pretreatment method will become mainstream in crop straws pretreatment.